2017
DOI: 10.1007/s40858-017-0152-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and levels of deoxynivalenol and zearalenone in commercial barley and wheat grain produced in Southern Brazil: an eight-year (2008 to 2015) summary

Abstract: Fusarium head blight (FHB), caused mainly by Fusarium graminearum, is one of the most important diseases of barley and wheat in Brazil. The disease causes yield losses and contaminates grain with mycotoxins produced by the fungus, mainly deoxynivalenol (DON) and zearalenone (ZEA). The objective of this study was to summarize the results of 16,487 analyses of DON and ZEA in barley and wheat commercial grain produced in Brazil from 2008 to 2015 using liquid chromatography tandem-mass spectrometry. For barley, DO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…This finding is most probably due to the presence of three of the most frequent Fusarium species in Europe, F. graminearum , F. poae and F. culmorum , e.g., [ 14 , 38 , 39 , 40 ], although the latter seems to be decreasing during the last decades [ 41 , 42 ]. Even on a global level, such as in Argentina, Australia, Brazil and Canada, these toxins are considered to be the most frequent ones in small-grain cereals [ 43 , 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding is most probably due to the presence of three of the most frequent Fusarium species in Europe, F. graminearum , F. poae and F. culmorum , e.g., [ 14 , 38 , 39 , 40 ], although the latter seems to be decreasing during the last decades [ 41 , 42 ]. Even on a global level, such as in Argentina, Australia, Brazil and Canada, these toxins are considered to be the most frequent ones in small-grain cereals [ 43 , 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intolerably, 11% and 7% of wheat samples were surpassed the EU regulatory limits of DON and ZEA, respectively, and found unfit for consumption. Similarly, Mallmann et al (2017) during 2008–2015 in Brazil have measured the prevalence of FHB and detected 73% and 38% of wheat samples, 67% and 41% of barley samples were contaminated with DON and ZEA, respectively. Furthermore, Kos et al (2017) in Serbia have noticed 260.1–1388, 260.4–9050, and 252.3–6280 μg/kg of DON in maize samples during 2013, 2014, and 2015, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In Hungary, Tima et al ( 2018 ) have surveyed the occurrence of DON in maize, wheat and its by-products during the period 2008–2015 and noticed overall mean of 2,159 ± 2,818 μg/kg, which was annoyingly much higher than maximum allowed limit. Besides, Mallmann et al ( 2017 ) have summarized the occurrence of DON and ZEA in barley and wheat grains of Southern Brazil during the middle of 2008–2015 and noticed 67% of DON and 41% of ZEA contamination. Similarly, Tralamazza et al ( 2016 ) have observed 99% of DON and 84% of ZEA contamination in wheat samples originated from Brazil.…”
Section: Introductionmentioning
confidence: 99%